PRECONCEPTION HEALTH COUNSELING AND STUNTING PREVENTION LITERATUR REVIEW - Sitti Salmiyah A. Bahruddin, Aminuddin Syam, Nurhaedar Djafar Suriah (Chelonian Research Foundation, 2024)
This paper presents the results of a literature review on the importance of preconception health counseling to prevent stunting in newborns. Literature searches refer to the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines. The literature in this study is mostly sourced from online journals accessed from scientific article sites with open access, such as ScienceDirect, PubMed and ProQuest. The strategy used was the PICOS framework, resulting in 171 articles. This article was then further analyzed in the title and abstract, and 12 eligible articles were obtained. Various interventions have been carried out to prevent stunting, including improving nutrition through nutrient supplementation. This nutrition intervention must be supported by various sensitive interventions such as education and counseling to improve community knowledge and skills in stunting prevention efforts. In some articles, it is found that counseling and counseling efforts must be carried out using directed and theory-based modules.